# Integration by Substitution

"Integration by Substitution" (also called "u-substitution") is a method to find an integral, but only when it can be set up in a special way.

The first and most vital step is to be able to write your integral in this form:

Note that you have **g(x)** and its derivative **g'(x) **

It might make more sense as is an example:

Here **f=cos**, and you have **g=x ^{2}** and its derivative of

**2x**

This integral is good to go!

If your integral is set up like that, then you can do this substitution:

Then you can integrate f(u), and finish by putting g(x) back as a replacement for u.

Like this:

### Example: ∫cos(x^{2}) 2x dx

We know (from above) that it is in the right form to do the substitution:

Now integrate:

∫cos(u^{}) du = sin(u) + C

And finally put **u=x ^{2}** back again:

sin(x^{2}) + C

So **∫****cos(x ^{2}) 2x dx = sin(x^{2}) + C** worked out really nicely! (Well, I knew it would.)

This method only works on some integrals of course, and it may need rearranging:

### Example: ∫cos(x^{2}) 6x dx

Oh no! It is **6x**, not **2x**. Our perfect setup is gone.

Never fear! Just rearrange the integral like this:

∫cos(x^{2}) 6x dx = 3∫cos(x^{2}) 2x dx

(We can pull constant multipliers outside the integration, see Rules of Integration.)

Then proceed as before:

3∫cos(u^{}) du = 3 sin(u) + C

Now put **u=x ^{2}** back again:

3 sin(x^{2}) + C

Done!

Now we are ready for a slightly harder example:

### Example: ∫x/(x^{2}+1) dx

Let me see ... the derivative of x^{2}+1 is 2x ... so how about we rearrange it like this:

∫x/(x^{2}+1) dx = ½∫2x/(x^{2}+1) dx

Then we have:

Then integrate:

½∫1/u du = ½ ln(u) + C

Now put **u=x ^{2}+1** back again:

½ ln(x^{2}+1) + C

And how about this one:

### Example: ∫(x+1)^{3} dx

Let me see ... the derivative of x+1 is ... well it is simply 1.

So we can have this:

∫(x+1)^{3} dx = ∫(x+1)^{3} · 1 dx

Then we have:

Then integrate:

∫u^{3} du = (u^{4})/4 + C

Now put **u=x+1** back again:

(x+1)^{4} /4 + C

So there you have it.

## In Summary

**u=g(x)**and integrate ∫f(u) du

**g(x)**where

**u**is.